Taxonomic Revision of Piptolepis (Vernonieae, Asteraceae) - Cândido, Jacqueline B.; Bicalho, Monira; Loeuille, Benoît (Phytotaxa, 2025)
Piptolepis comprises 19 species, all of them endemic to the mountains of the state of Minas Gerais, Brazil. It is characterized by the shrub to treelet habit, with densely branched stems, marked by leaf scars and covered by dense indumentum. The leaves are alternate, spiraled, discolorous, with a typical pad-like leaf sheath. The capitula are solitary, or organized in a terminal raceme, pseudoglomerule or rarely in a corymb. Most of the species (16) are microendemic and known from few populations. Thereby, the genus should be considered a priority for conservation. The main goal of this study is to present the first taxonomic revision of the genus since the 19th century, providing access to updated and detailed information of all species of Piptolepis. This revision describes four new species (P. elaeodes, P. fulgens, P. redacta and P. speciosa) and provides complete synonymies, descriptions, conservation status, illustrations, discussion of taxonomic affinities, distribution maps, and an identification key.